The Potential of Waqf Land In Addressing the Housing Backlog in Indonesia (Contributions, Feasibility, Affordability) - Cupian Cupian; Pidi Apriyadi; Sarah Annisa Noven (UPT Publikasi Ilmiah UNISBA, 2026)
The housing backlog remains a significant challenge in Indonesia, leading to multifaceted issues, including social, economic, and environmental problems. Conventional programs aimed at reducing this backlog have yet to fully address the issue. As an alternative solution, waqf land, an instrument of development in Islamic economics, presents a promising potential to alleviate the housing backlog. This study aims to assess the potential of waqf land to reduce the housing backlog. Under different allocation schemes, the potential waqf land for housing in Indonesia is estimated to be 28.63 million m² under the 5% scheme, 42.95 million m² under the 7.5% scheme, and 57.26 million m² under the 10% scheme. The contribution of waqf land to reducing the housing backlog varies across these schemes, with the highest contribution reaching up to 241.74%. At the national level, the housing model is found to be feasible in aggregate, and the type 21/60 waqf-based housing initiative is affordable under the subsidized scheme across all provinces, while the non-subsidized scheme remains affordable only in several regions.